Close reading of 'A monument full of stories' (Bulletin KNOB, 2011)
There are many different definitions and interpretations of the concept of authenticity, but the authenticity discourse appears to be unsuitable as an interpretation framework for the exhibition 'A monument full of stories' in Rotterdam Laurenskerk. Not only was the greater part of the church itself newly constructed in the old style after the bombing in 1940, but the exhibition, too, was made with new materials and modern media. The theory of performativeness, however, does offer a good alternative to analyse the functioning and the effects of this exhibition. According to this theory a difference is made between constative and performative statements. Constative statements ascertain something, performative statements see to it that something happens. When applied to exhibitions, this implies that a constative presentation especially aims at conveying the truth of the object presented. This entails a certain reserve, both in the form of the presentation and in the information supplied on it.Performative presentations, on the other hand, are not aimed at truths, but at experiences. It is not a question of one true story, but of various perspectives, stories, types of expertise. It is not the objects that are focused on, but the story told with the aid of objects - stage properties. A constative exhibition is characterized by material authenticity, a performative one by a narrative authenticity. Thus the distance between expert and visitor, between space, object and information is bridged. The role of the audio guide in Laurenskerk is typical for the performative character of the exhibition. There is no omniscient narrator, but there are various narrators around one theme, the listener is part of an unfinished, incomplete conversation on this theme. Information is alternated with music and personal stories; there are also many things that the visitor himself can do, grip, touch. Information, education and evocation change places. The past is not so much reproduced as performed, in a dramatic, cinematic way. Monumental churches rarely excel in the presentation of their heritage. Financial investment in an optimal presentation of heritage is often too expensive, or weighing the pros and cons of the religious interests of the churchgoers against the tourist interests of the visitors is decided in favour of the church community.In the exhibition 'A monument full of stories' the tension between the religious and the secular is never absent, incorporated in the larger narrative of Laurenskerk itself, which survived the Second World War severely harmed. It is not an exhibition in a church, but the church itself has turned into an exhibition. In an adventurous way history and the meaning of Laurenskerk are revealed, taking advantage of contemporary visual culture and media culture. Although the greater part of the churches have become cultural heritage, even nowadays religion is still alive and determines society. The border between where secular life starts and where the religious ends, is not easy to draw, and should be discussed. That is what this exhibition has achieved, in a performative sense.